HAKIKAT SAINS DAN EPISTEMOLOGI ISLAM DALAM KURIKULUM BERBASIS PEMBARUAN DI SMP AL-IRSYAD SURAKARTA - Yusuf Arifin; Mujiburrohman (LPPM Universitas Cipta Mandiri, 2026)
This field research aims to analyze the integration of the essence of science and Islamic epistemology within a renewal-based curriculum at SMP Al-Irsyad Surakarta. The school possesses a unique historical-ideological character as it adopts the anti-taqlid renewal spirit (tajdid) of Ahmad As-Surkati amid the demands of 21st-century digitalization. Employing a descriptive qualitative method with a field research case study approach, primary data were collected through semi-structured in-depth interviews with the Principal, Vice Principal for Curriculum Affairs, and science and Islamic Religious Education (PAI) teachers. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings reveal that SMP Al-Irsyad Surakarta constructs the essence of science not as a mechanistic secular entity, but as an empirical reading of cosmic verses (ayat kauniyah). Islamic epistemology is actualized through the unification of the burhani method (rational-experimental analysis) and the bayani method (scriptural guidance). The curriculum is realized through integrative teaching material clustering, where general scientific formulas are traced to their theological roots without indiscriminately conflating disciplinary domains. This research provides a practical contribution regarding the operationalization model of science-Islam integration at the junior secondary school level.